Теоретическая (предельная) твердость - Фирстов, С.А.; Рогуль, Т.Г. (Видавничий дім "Академперіодика" НАН України, 2007)
A new concept, theoretical (limit) hardness, is suggested for quick and effective estimations of the maximum possible hardening of materials, and the formula for its calculation is derived. The estimated values of the theoretical hardness of some materials are analyzed.